Analysis of the effects of group progressive resistance training on inflammatory markers, cardiovascular fitness parameters, and respiratory function in elderly patients with chronic obstructive pulmonary disease - Chunyang Li; Yijia Sun (Journal of Medical Biochemistry)
Background: To investigate the effects of implementing group progressive resistance training on Maximal Oxygen consumption (VO2max), Maximum Ventilation per minute (VEmax), Maximal Oxygen pulse (O2pulsemax), Maximum Heart Rate (HRmax), and Modified Medical Research Council dyspnea scale (mMRC) in elderly patients with chronic obstructive pulmonary disease. Methods: A total number of 114 elderly patients with chronic obstructive pulmonary disease treated in the hospital from May 2022 to May 2024 were collected and divided into two groups based on different training methods. The conventional group (n=57) received routine rehabilitation training, while the organization group (n=57) received group progressive resistance training. Cardio - pulmonary Exercise Testing (CPET) parameters, serum inflammatory factors, lung function indicators, and mMRC score were compared between two groups before training, 2 weeks of training, and 4 weeks of training. Results: Before training, there was no significant difference between the two groups regarding training compliance, CPET parameters, inflammatory factors, and mMRC score. After 2-4 weeks of training, both groups showed improvements in training frequency, intensity, autonomous training, and increases in VO2MAX, VEmax, O2pulsemax, and HRmax. However, the organization group had higher scores in these areas and lower levels of inflammatory factors (IL-8, IL-18, IL-6, IL-12) and mMRC scores compared to the conventional group, with statistically significant differences (P<0.05). Conclusions: Group progressive resistance training can help improve the compliance of elderly patients with chronic obstructive pulmonary disease with training, reduce the body's inflammatory response, improve VO2MAX, VEmax, O2pulsemax, and HRmax levels, and alleviate breathing difficulties.